SURGICAL CLOSURE OF HEMODYNAMICALLY SIGNIFICANT PDA IN VERY LOW BIRTH WEIGHT PRETERM NEONATE: A CASE REPORT AND LITERATURE REVIEW : Surgical PDA Closure in VLBW Preterm Neonate - Rahman, Aditya; Soebroto, Heroe; Hakim, Arief Rakhman (Journal of Neonatal Surgery, 2025)
Background: Patent ductus arteriosus (PDA) is a common problem in preterm neonates, particularly when it is hemodynamically significant or "large" in size. Its persistence may result in severe cardiopulmonary and systemic compromise. Case Presentation: We present a case of a neonate born at 27 weeks’ gestation weighing 1150 grams, diagnosed with a large PDA (4 mm) and associated septal defects. The patient had severe comorbidities including neonatal sepsis due to multidrug-resistant (MDR) organisms, pneumonia, malnutrition, congenital hypothyroidism, and suspected Hirschsprung disease. Medical management was contraindicated, and surgical ligation was performed at day 34 via posterolateral thoracotomy. Postoperative recovery was marked by improvement in hemodynamics, respiratory status, and nutritional tolerance. Patient was discharged 44 days after surgery in stable condition and grew well. Conclusion: This case illustrates the clinical benefit and safety of surgical PDA ligation in a critically ill, extremely preterm infant when pharmacologic options are not viable. Timely intervention and multidisciplinary care were crucial in achieving a favorable outcome. Keywords: large patent ductus arteriosus, very low birth weight, premature infant, surgical ligation